Acquisition of academic literacy in an Engineering communication course: Integration of English for Specific Purposes (ESP) and Systemic Functional Linguistics (SFL) - Merina Devira (Universitas Syiah Kuala, 2017)
This study investigated academic literacy practices by an EFL student at an Engineering Communication course in the University of Adelaide, Australia. It focused on finding a description of engineering written communication skills designed in the specific course and investigating the student's response in the construction of a specific text type in the engineering community. A qualitative case study method was used where the data were taken from classroom observations, the student's interviews, his writings, and other supporting data, such as a course booklet and several PowerPoint slides. The findings showed that working in a group discussion at the workshop sessions was perceived as the most useful academic literacy practice in acquiring engineering communication skills. It also revealed that academic literacy practices, such as accessing MyUni, using databases for a specific discipline, recognising graphic skills and using effective reading strategies were considered by him as new and useful practices in an academic culture which helped him execute written engineering communication assignments into a cohesive and coherent argumentative text. Overall, although he had different perceptions before and after completion of the course, he viewed the course design positively. Some ideas on how the course developers or tutors could match the course design with his practical needs were offered, such as mutual collaboration with the English lecturers who were providing the course and the implementation of a program of academic English for first year students.